Resistance to Sharka in Apricot: Comparison of Phase-Reconstructed Resistant and Susceptible Haplotypes of ‘Lito’ Chromosome 1 and Analysis of Candidate Genes - De Mori, Gloria; Falchi, Rachele; Testolin, Raffaele; Bassi, Daniele; Savazzini, Federica; Dondini, Luca; Tartarini, Stefano; Palmisano, Francesco; Minafra, Angelantonio; Spadotto, Alessandro; Scalabrin, Simone; Geuna, Filippo (Frontiers in Plant Science, 2019)
Sharka, a common disease among most stone fruit crops, is caused by the Plum Pox Virus (PPV). Resistant genotypes have been found in apricot (Prunus armeniaca L.), one of which – the cultivar ‘Lito’ heterozygous for the resistance – has been used to map a major QTL on linkage group 1, following a pseudo test-cross mating design with 231 individuals. In addition, 19 SNP markers were selected from among the hundreds previously developed, which allowed the region to be limited to 236 kb on chromosome 1. A ‘Lito’ BAC (Bacterial Artificial Chromosome) library was produced, screened with markers of the region, and positive BAC clones were sequenced. Resistant (R) and susceptible (S) haplotypes were assembled independently. To refine the assembly, the whole genome of ‘Lito’ was sequenced to high coverage (98X) using PacBio technology, enabling the development of a detailed assembly of the region that was able to predict and annotate the genes in the QTL region. The selected cultivar ‘Lito’, allowed not only to discriminate structural variants between the two haplotypic regions, but also to distinguish specific allele expression, contributing towards mining the PPVres locus. In the light of these findings, genes previously indicated (i.e. MATHd genes) to have a possible role in PPV resistance were further analysed, and new candidates were discussed. Although the results are not conclusive, the accurate and independent assembly of R and S haplotypes of ‘Lito’ is a valuable resource to predict and test alternative transcription and regulation mechanisms underpinning PPV resistance.